GRAPHICS – THE ESSENTIAL TOOL IN LOGO DESIGN - Ovidiu Nicolaescu (Journal of Industrial Design and Engineering Graphics, 2020)
The logo is one of the most important elements of the company’s visual promoting strategy. Even so, the creation of a logo which fulfils all the specific criteria of an ideal logo can be a tough process given the fact that the market and trends are changing continuously. The actual paperwork focus on the study of graphics, on its influence in logo designing process but also it focuses on the analysis of existent brands and their possible redesigns with implications over population’s opinion.